1988
DOI: 10.1212/wnl.38.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Familial cavernous angiomas of the brain in an Hispanic family

Abstract: We found cavernous angiomas (CA) in 10 of 22 members of a large Hispanic family. The proband had seizures, and a CA was found at surgery. He and two sisters with seizures had normal angiograms, but CT or MRI showed lesions compatible with CA. Similar abnormalities were found in two cousins with seizures and 5 of 17 asymptomatic relatives studied. MRI proved to be more sensitive than CT for identifying CA. Hispanic families appear to have a predisposition for dominantly inherited CA of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…They documented autosomal dominant inheritance with variable expressivity. This report was followed by the studies of Rigamonti et al 47 and Mason et al 36 who found that familial inheritance was especially high in Hispanic-American families.…”
Section: Risk Factors That Increase Hemorrhage Riskmentioning
confidence: 81%
“…They documented autosomal dominant inheritance with variable expressivity. This report was followed by the studies of Rigamonti et al 47 and Mason et al 36 who found that familial inheritance was especially high in Hispanic-American families.…”
Section: Risk Factors That Increase Hemorrhage Riskmentioning
confidence: 81%
“…Not all CCM are associated with symptoms, but once they become symptomatic 40 to 50 percent present with seizures, 20 percent with focal neurological deficit, and 9-10 percent with hemorrhage [1,2] . The risk of hemorrhage has been estimated between 0.2and 2.5% per lesion per year [3] . These number may be higher for patients with brain stem CCM [4] and the symptoms may worse when it occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the lesions are supratentorial in location.However,in 10-25% are infratentorial(the cerebellum or brain stem). According to the MRI study of autopsied cases, cavernoma exists in 0.4-0.7% of all subjects .They are often found in 3-5 decades and multiple CCMs are seen about 15-50% (up to 80% of affected family members) of patients [3,5] . Familial form is inheritated as an autosomal dominant trait with variable expression.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in the late eighties, familial cavernous malformations were reported to be more common among "Hispanics." 34,35 However, more precise research showed linkage of these cavernous malformations to chromosome 7q11-22 in 4 unrelated Mexican families that might share a common ancestor in Sonora County, Mexico. 36 We now also know that "white" 37 and "Italian-American" 38 families with cavernous malformations may show the same or other linkages, for example, to chromosomes 7p13-15 and 3q25.2-27.…”
mentioning
confidence: 99%